EMULATION OF SOFTWARE-DEFINED NETWORK USING MININET - Do Van Khoa; Tran Ngo Nhu Khanh (Tạp chí Khoa học Đại học Đà Lạt)
Software-defined networking (SDN) represents a new structure of computer network that simplifies and improves network management by splitting the control plane and data plane. Since SDN is regarded as a new research issue, the application of SDN in practice faces some barriers. Most network devices such as routers and switches that implement SDN functionalities are expensive. An alternative solution in SDN research and experiments is to use network emulators. By using Mininet, an open source network emulator, this study simulates SDN implementations in different environments. Results show that the simulation environment affects building network topology time.